Aspek Hukum Penyelesaian Sengketa Tanah Adat - Myaskur Myaskur; Tri Wahyudiono (Universitas Pangeran Diponegoro Nganjuk, 2024)
In Indonesia, the resolution of customary land disputes involves a complex interplay between customary law and national law. Customary law, deeply rooted in the cultural practices and traditions of indigenous communities, plays a crucial role in managing land conflicts that arise within these communities. This paper examines the legal aspects of resolving customary land disputes, highlighting the significance of integrating customary law into the national legal framework to ensure the protection of indigenous rights. The study reveals that while national laws provide a formal mechanism for dispute resolution, they often overlook the unique cultural contexts and values inherent in customary law. Consequently, this can lead to unresolved conflicts and dissatisfaction among indigenous peoples. The research suggests that a hybrid model of dispute resolution, which combines elements of both customary and national law, could enhance the effectiveness of conflict resolution processes. By recognizing and legitimizing customary practices within the national legal system, this approach aims to promote social justice and equity for indigenous communities in Indonesia.